2012
DOI: 10.1088/0022-3727/45/19/195301
|View full text |Cite
|
Sign up to set email alerts
|

High pyroelectricity in lead-free 0.5Ba(Zr0.2Ti0.8)O3–0.5(Ba0.7Ca0.3)TiO3 ceramics

Abstract: We report high pyroelectricity in lead-free 0.5Ba(Zr0.2Ti0.8)O3–0.5(Ba0.7Ca0.3)TiO3 (BZT–50BCT) ceramics which were previously reported to exhibit high piezoelectricity. The pyroelectric coefficient measured by the Byer–Roundy method upon heating for dc-poled samples shows a high value of 5.84 × 10−4 C m−2 K−1 at 300 K, comparable to those of PZT-based ceramics and significantly higher than many other lead-free pyroelectric materials. The pyroelectric coefficient calculated from the remanent polarization versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 25 publications
2
36
1
Order By: Relevance
“…The dielectric permittivity value $2600 at room temperature is consistent with earlier reports. 28,30,33 It is also observed that the permittivity exhibits a frequency independent behavior, indicating that the studied sample is not a typical relaxor ferroelectric. Moreover, a polymorphic phase transition (PPT) between rhombohedral and tetragonal phase takes place near room temperature (indicated by an arrow) followed by a tetragonal to cubic transition with 97 C as the temperature of maximum permittivity (T m ).…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…The dielectric permittivity value $2600 at room temperature is consistent with earlier reports. 28,30,33 It is also observed that the permittivity exhibits a frequency independent behavior, indicating that the studied sample is not a typical relaxor ferroelectric. Moreover, a polymorphic phase transition (PPT) between rhombohedral and tetragonal phase takes place near room temperature (indicated by an arrow) followed by a tetragonal to cubic transition with 97 C as the temperature of maximum permittivity (T m ).…”
Section: Methodsmentioning
confidence: 88%
“…27 Yao et al reported high pyroelectricity (5.84 Â 10 À4 C m À2 K À1 at room temperature) in this system. 28 Damjanovic et al reported Raman spectra and temperature induced anomalies in dielectric and elastic coefficients of BCZT. 29 Li et al reported the dielectric properties of BCT-BZT as a function of Ca-doping.…”
mentioning
confidence: 99%
“…As is well known, infrared sensors made of ferroelectric materials exhibit great advantages of uncooled operation, high sensitivity, broad spectral response range and low cost compared with photon detectors and are widely used in alarms, thermal imaging and intruder imaging [4][5][6]. Thin film ferroelectric infrared detectors and focal plan arrays are expected to yield better sensitivities and faster response than equivalent ceramics and bulk single crystals, and can be deposited directly on silicon readout integrated circuitry [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, their performances are far from being satisfactory enough to replace PZT. Recently, Yao et al [6] reported high pyroelectricity of 17.17 Â 10 À 4 C m À 2 K À 1 at 300 K in lead-free 0.5BaZr 0.2 Ti 0.8 O 3 -0.5Ba 0.7 Ca 0.3 TiO 3 (abbreviated as BCZT50), which is comparable to those of PZT-based ceramics and higher than many other lead-free pyroelectric materials, making it a promising material for pyroelectric detector applications. The understanding of the optical properties of BCZT thin films in infrared region is significant to optimize the device fabrication and improve the potential performance of thin-film infrared pyroelectric detectors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liu and Ren [10] reported the 0.5BaZr 0.2 -Ti 0.8 O 3 -0.5Ba 0.7 Ca 0.3 TiO 3 (BCZT50) with morphotropic phase boundary (MPB) starting from a critical triple point of a cubic paraelectric phase (C), ferroelectric rhombohedral (R), and tetragonal phase (T). Great efforts have been made to investigate the microstructure, phase-transition and dielectric, pyroelectric, piezoelectric properties of BCZT50 ceramics [11][12][13][14][15][16][17][18]. But scare systematic research about its optical parameters is reported now.…”
Section: Introductionmentioning
confidence: 99%